2021
DOI: 10.3390/healthcare9081029
|View full text |Cite
|
Sign up to set email alerts
|

Child Fluoride Varnish Programs Implementation: A Consensus Workshop and Actions to Increase Scale-Up in Australia

Abstract: This paper presents the findings of the National Fluoride Varnish Workshop in 2018 along with subsequent actions to scale-up the use of fluoride varnish nationally in Australia. The use of fluoride varnish programs to prevent dental caries in high-risk child populations is an evidence-based population health approach used internationally. Such programs have not been implemented at scale nationally in Australia. A National Fluoride Varnish Consensus Workshop was held in Sydney in November 2018 with an aim of sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Current fluoride varnish programs in NT are limited in their reach and effectiveness for the prevention of dental caries and have not consistently reached individuals within therapeutically appropriate intervals. 12,38 Programs for regular application of topical fluoride in children at high risk of dental caries should continue to occur as part of current developmental screening and preventive services, irrespective of CWF. Additionally, like previous studies, this study did not consider impacts of potential dental fluorosis, which is a cosmetic condition caused by overexposure to high fluoride levels (>1 mg/L) during tooth formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current fluoride varnish programs in NT are limited in their reach and effectiveness for the prevention of dental caries and have not consistently reached individuals within therapeutically appropriate intervals. 12,38 Programs for regular application of topical fluoride in children at high risk of dental caries should continue to occur as part of current developmental screening and preventive services, irrespective of CWF. Additionally, like previous studies, this study did not consider impacts of potential dental fluorosis, which is a cosmetic condition caused by overexposure to high fluoride levels (>1 mg/L) during tooth formation.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, our study did not quantify the impacts of topical and adjunctive fluoride supplements (such as toothpaste, mouthrinse, professionally applied gels, foams or fluoride varnish). Current fluoride varnish programs in NT are limited in their reach and effectiveness for the prevention of dental caries and have not consistently reached individuals within therapeutically appropriate intervals 12,38 . Programs for regular application of topical fluoride in children at high risk of dental caries should continue to occur as part of current developmental screening and preventive services, irrespective of CWF.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, fluoride varnish is a Schedule 4 medicine under the Therapeutic Goods Administration and restricted to use by registered medical practitioners but is considered Schedule 3 when used by registered dental practitioners. Various states and territories have revised their drugs and poisons regulations to enable registered non-dental practitioners and unregistered health professionals to use fluoride varnish ( Skinner et al ., 2021 ). For example, Aboriginal Health Workers and nurses in the Northern Territory and Western Australia are authorized access to apply fluoride varnish to children ( Nguyen, 2017 ).…”
Section: Enabling Universal Health Coverage That Includes Oral Healthmentioning
confidence: 99%
“…The beneficial role of fluoride in the primary prevention of dental caries has been demonstrated by numerous studies. The main mechanisms by which fluoride fulfills this role are based on inhibiting demineralization and promoting the remineralization of dental hard tissues, as well as on the antibacterial effect of inhibiting enolase, the enzyme necessary for bacteria to metabolize carbohydrates [ 2 , 3 , 4 , 5 , 6 ]. It has been shown that, by this mechanism, fluoride varnishes can reduce the number of cariogenic bacteria ( S. mutans ) by more than ten times [ 7 ].…”
Section: Introductionmentioning
confidence: 99%